2021
DOI: 10.16899/jcm.945345
|View full text |Cite
|
Sign up to set email alerts
|

Anjiyojenik protein Cyr61’in ekspresyonu, erken başlangıçlı preeklampsi hastalarının idrarında önemli ölçüde artar

Abstract: This study sought to compare the expression of the Cysteinerich 61 (Cyr61) protein in the urine of early-onset preeclampsia (PE) patients with that of the urine of normotensive healthy pregnant women. Material and Method:A total of 80 patients who gave birth from June 2019 to December 2019 were enrolled in this prospective study. The study group comprised 40 pregnant women at 20-34 weeks of gestation who presented with early-onset PE. Gestational age-and body mass index-matched, 40 healthy normotensive pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Inflammation‐oxidative stress axis acts a crucial role in the pathogenesis of diverse obstetric complications, including PPROM 16,27–30 . The prognostic value of systemic inflammatory markers, including NLR and PLR, in many diseases, such as early pregnancy loss, membrane rupture, and HCA, has already been demonstrated in several studies 19,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation‐oxidative stress axis acts a crucial role in the pathogenesis of diverse obstetric complications, including PPROM 16,27–30 . The prognostic value of systemic inflammatory markers, including NLR and PLR, in many diseases, such as early pregnancy loss, membrane rupture, and HCA, has already been demonstrated in several studies 19,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…During a healthy pregnancy, the balance between T helper 1 (Th1) and Th2 immune cells and their immune responses is crucial for maintaining gestation. 18,19 A healthy pregnancy is thought to be a state with Th2 predominance, which provides an immunotolerant setting for fetal rejection prevention. 20 However, in preeclamptic patients, placental ischemia as a result of shallow trophoblast invasion increases proinflammatory CD4+ T cells and reduces regulatory T helper cells.…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, the incidence is two per 1000 live births, while ranges between 3.1%–56.9% in African countries 3,4 . Previous studies reported numerous contributing factors of birth asphyxia, including antepartum risk factors (gestational hypertensive disorders, advanced maternal age, adolescent pregnancies, antepartum hemorrhage, anemia, low educational status, history of neonate with birth asphyxia), intrapartum risk factors (giving birth at home, the prolonged second stage of labor, malpresentation, meconium‐stained amniotic fluid [MSAF]), and fetal risk factors (fetal distress, preterm birth, tight nuchal cord, multiple pregnancies) 5–10 …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Previous studies reported numerous contributing factors of birth asphyxia, including antepartum risk factors (gestational hypertensive disorders, advanced maternal age, adolescent pregnancies, antepartum hemorrhage, anemia, low educational status, history of neonate with birth asphyxia), intrapartum risk factors (giving birth at home, the prolonged second stage of labor, malpresentation, meconium-stained amniotic fluid [MSAF]), and fetal risk factors (fetal distress, preterm birth, tight nuchal cord, multiple pregnancies). [5][6][7][8][9][10] Birth asphyxia refers to a blood flow interruption to the placenta in the period immediately before, during, or following the delivery process, leading to hypoxia and ischemia. If the lack of blood flow persists for quite a while, it may cause persistent neurologic damage, which may ultimately evolve into neurodevelopmental disorders, including neurodevelopmental delay, intellectual disabilities, seizures, hypoxic-ischemic encephalopathy (HIE), and cerebral palsy.…”
Section: Introductionmentioning
confidence: 99%